Czerwony Kapturek. Kobiecość (nie)ujawniona – interpretacyjne prowokacje - Gromkowska-Melosik , Agnieszka (Studia Edukacyjne, 2017)
The author of the article reconstructs the various concepts of femininity in the fable Red Riding Hood. The main thesis is related to conviction that fables including Red Riding Hood are the fieldof specificcrystallization of culture uncertainity. In the case of Red Riding Hood competing interpretations of meanings are deconstructed. One can give here as an example the feminist understanding of Red Riding Hood, postmodern approach to this fascinating heroine and power girl related thinking, as well as psychoanalytic concepts. So in the seemingly naïve and banal fable various version of femininity and feminine sexuality can be discovered.